Community Social Empowerment Through Basic Food Assistance Activities Based On Lecturers And Students At The Nurul Hidayah Batam Foundation - Tito Pratama; Dailami Dailami; Moh. Thandzir; Syafruddin Rais; Wahyudi Ilham; Siska Amelia Maldin; Haufi Sukmamedian; Bojes Ariansya (JURNAL KEKER WISATA, 2026)
Community Service Activities (PKM) with the title "Social Service for the Distribution of Basic Necessities" is a form of social concern that aims to help people in need, especially in meeting daily basic needs. This activity is carried out by distributing food packages to underprivileged communities, orphanages, or other vulnerable groups. The implementation of activities is carried out through the planning stages, collecting data on beneficiaries, and distributing aid directly so that it is right on target. In addition, this activity also involves the active participation of students, lecturers, and related parties as a form of implementation of the values of mutual cooperation and social concern. The results of this activity show that the assistance provided can ease the economic burden on the community and strengthen the relationship between universities and the community. This activity also provides real experience for students in implementing humanitarian values and service. Thus, this PKM activity is expected to provide short-term benefits in the form of assistance for basic needs, as well as long-term benefits in the form of increased empathy, social solidarity, and concern for others in community life.